2020
DOI: 10.1073/pnas.1922076117
|View full text |Cite
|
Sign up to set email alerts
|

The Whi2p-Psr1p/Psr2p complex regulates interference competition and expansion of cells with competitive advantage in yeast colonies

Abstract: Yeast form complex highly organized colonies in which cells undergo spatiotemporal phenotypic differentiation in response to local gradients of nutrients, metabolites, and specific signaling molecules. Colony fitness depends on cell interactions, cooperation, and the division of labor between differentiated cell subpopulations. Here, we describe the regulation and dynamics of the expansion of papillae that arise during colony aging, which consist of cells that overcome colony regulatory rules and disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…This finding was confirmed in the study of Szamecz et al [8], who found that the WHI2 deletion is very weakly deleterious; these researchers also found a compensatory effect of WHI2 inactivation during evolution of a rpb9Δ strain. In contrast, in other environmental conditions (in dense colonies and upon nutrient deprivation), deletion of WHI2 is beneficial [67]. In unstable landscapes, loss-of-function mutations of WHI2 are frequently observed [68].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed in the study of Szamecz et al [8], who found that the WHI2 deletion is very weakly deleterious; these researchers also found a compensatory effect of WHI2 inactivation during evolution of a rpb9Δ strain. In contrast, in other environmental conditions (in dense colonies and upon nutrient deprivation), deletion of WHI2 is beneficial [67]. In unstable landscapes, loss-of-function mutations of WHI2 are frequently observed [68].…”
Section: Discussionmentioning
confidence: 99%
“…Although sla1Δ cells are deficient for leucine uptake, their slow growth can not be overcome by increasing the concentration of leucine in EMM, consistent with it its uptake inhibitition by NH4 + [50]. A striking characteristic was an apparent communal effect of the SSR mutants on the growth of their otherwise isogenic neighbors [95,96]. As the SSRs emerged as rare mutants from the sla1Δ cells they were surrounded by smaller sattelite colonies (Fig 3A and 3B).…”
Section: Spontaneous Sla1δ Revertants (Ssrs) Of Slow Growth Relieve Inhibitition By Nh4 + On Leucine Uptakementioning
confidence: 78%
“…To obtain images of whole colonies we combined two images from neighboring fields of view. For fluorescence microscopy, thin sections were prepared from colonies embedded in 3% agarose using a Leica VT1200S vibrating microtome (Leica, Wetzlar, Germany) [ 14 , 47 ] and observed by an Axio Observer.Z1 fluorescence microscope (Carl Zeiss, Oberkochen, Germany) equipped with an Axiocam 506 and an Apochromat 10×/0.45W objective or an Apochromat 63×/1.20 W using ZEN 2012 (blue edition) software. Filter sets for GFP fluorescence: 450–490 nm and 500–550 nm for excitation and emission, respectively.…”
Section: Methodsmentioning
confidence: 99%